The Effect of Digital Literacy on Entrepreneurial Intention through Entrepreneurial Attitude - Mustain, Mustain; Murwani, F. Danardana; Mukhlis, Imam Mukhlis (PT FORMOSA CENDEKIA GLOBAL, 2023)
The lack of Vocational High School graduates who have an entrepreneurial spirit and entrepreneurial intentions and can create new businesses is where the role of digital literacy in entrepreneurship education is needed which is expected to provide a theoretical basis for the concept of entrepreneurship, forming the mindset, attitudes, and behavior of an entrepreneur. This study uses a quantitative approach with Partial Least Squares (PLS-SEM) structural equation modeling to predict and confirm the hypotheses given. This study uses Google Forms for data collection on private vocational students in Mojokerto Regency. Respondents in this study were 150 respondents from the three schools used as research objects. The results showed that Digital Literacy can explain Entrepreneurial Attitude and Entrepreneurial Intention.